PENGARUH MOTIVASI KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN PADA CV. BHUWANA PERMAI - Ni Wayan Vina Purnama Dewi; Anak Agung Dwi Widyani; Tiksnayana Vipraprastha (VALUES, 2022)
Companies need to make efforts to improve employee performance because the company's survival is very dependent on the quality of employee performance. This study aims to determine the effect of work motivation and Organizational Citizenship Behavior (OCB) on employee performance at CV. Bhuwana Permai. This research was conducted at CV. Bhuwana Permai which is located at Br. Pande Kel. Sempidi, Kec. Mengwi, Kab. Badung. With the object of research on work motivation, Organizational Citizenship Behavior (OCB) and employee performance, the population in this study is all employees of CV. Bhuwana Permai, totaling 60 people. In this study to find the size or size of the sample, the technique used is a saturated sampling technique, so that the number of samples is 60 people. The data analysis technique used is instrument test, classical assumption and multiple linear regression analysis. The results of this study indicate that work motivation has a positive and significant effect on employee performance at CV. Bhuwana Permai with a tcount of 4.446 and a significant value of 0.000 <0.05. Organizational Citizenship Behavior has a positive and significant effect on employee performance at CV. Bhuwana Permai with a tcount of 3.690 and a significant value of 0.001 <0.05. Work Motivation and Organizational Citizenship Behavior simultaneously have a significant relationship to employee performance at CV. BhuwanaPermai with an F value Count of 175,578 with a significance value of 0.000 < 0.05.